Advanced energy conversion strategies using multistage radial turbines in Organic Rankine Cycles for low-grade heat recovery - Fuhaid Alshammari; Ahmed S. Alshammari; Ahmed Alzamil (Case Studies in Thermal Engineering)
The transition from fossil fuels to renewable energy is a critical process that demands technological advancements in energy conversion systems. Among these, the Organic Rankine Cycle (ORC) has emerged as a promising solution for harnessing low-grade heat sources such as solar and geothermal energy. A crucial component of ORC systems is the turbine, which dictates overall efficiency and power output. Conventional single-stage supersonic radial turbines suffer from shock waves and performance deterioration due to high pressure ratios. This study presents a novel approach by designing a multistage subsonic radial inflow turbine as an alternative, mitigating inherent losses in supersonic configurations. The key novelty lies in the development and validation of a detailed design methodology for multistage subsonic radial turbines, a relatively unexplored area in the literature. The study compares the performance of single-stage and multistage configurations across various working fluids and operating conditions, demonstrating significant efficiency improvements. Using R365mfc as the working fluid, the multistage turbine achieves 9 % higher power output and 9.29 % greater thermal efficiency than the single-stage design. By improving turbine efficiency and system adaptability, this study provides a practical framework for optimizing ORC performance, contributing to the transition toward cleaner energy solutions.